Spiritual Emotional Freedom Technique (SEFT) terhadap Tekanan Darah pada Pasien Hipertensi - Kurnia, Vera; Pauzi, Muhhammad; Ramadanti, Tika; Gusmiati, Rita; Fitri, Soffi Durratuzzahro (Jurnal Kesehatan Holistic, 2023)
Introduction: Hypertension become a major problem in many countries in the world and it the etiologies of cardiovascular. Nursing intervention performed in hypertension using complementary Technique that focus on their physical, emotional and spiritual respons. Spiritual Emotional Freedom Technique provides a light taping on the body's 18 meridian points that intends to stimulate and activate, resulting a relaxing effect on the body. Objective: The purpose of study to find the Effect of Spiritual Emotional Freedom Technique on Blood Pressure in people with Hypertension in area Rasimah Ahmad Health Center at Bukittinggi City in 2021. Methods: This type of quantitative research using pre-experimental (One group pretest-posttest). sample in 19 respondents. Non-Probability Sampling techniques and data collection using observation sheets and computerized processing. The meaningful values for the four data groups are not normal distribution. Statistic tes used Wilcoxon signed rank test. Result: The average systolic blood pressure before seft therapy is 141.32 mmHg and diastolic is 93.42 mmHg and the average systolic blood pressure after seft therapy is 136.58 mmHg and diastolic is 88.58 mmHg. The results of Wilcoxon Test obtained statistics obtained systolic value p = 0.003 and diastolic value p = 0.001, ? =0.05 (p<?), there is a meaningful change blood pressure in people with hypertension. Conclusion: Health care be used as a foundation for realizing evidence based practice in handling people with hypertension with complementary therapies.